"Batch" Kinetics in Flow: Online IR Analysis and Continuous Control1. (29th November 2013) - Moore, Jason S.; Jensen, Klavs F.
Abstract Currently, kinetic data is either collected under steady‐state conditions in flow or by generating time‐series data in batch. Batch experiments are generally considered to be more suitable for the generation of kinetic data because of the ability to collect data from many time points in a single experiment. Now, a method that rapidly generates time‐series reaction data from flow reactors by continuously manipulating the flow rate and reaction temperature has been developed. This approach makes use of inline IR analysis and an automated microreactor system, which allowed for rapid and tight control of the operating conditions. The conversion/residence time profiles at several temperatures were used to fit parameters to a kinetic model. This method requires significantly less time and a smaller amount of starting material compared to one‐at‐a‐time flow experiments, and thus allows for the rapid generation of kinetic data.